Comparison of Pre-Operative Cone Beam CT and Surgical Observations of the Oval Window Niche in Otosclerosis - .G, Agaman; .M. K, Rajasekar; .K, Ajitha (Journal of Neonatal Surgery, 2025)
Introduction: Otosclerosis is a progressive otic capsule disorder characterized by stapes footplate fixation leading to conductive hearing loss. Accurate identification of the oval window niche anatomy is critical in surgical planning for otosclerosis. Cone beam computed tomography (CBCT) has emerged as a valuable preoperative imaging tool due to its superior spatial resolution and lower radiation exposure compared to traditional CT. Materials & Methods: A prospective comparative study was conducted on 50 otosclerosis patients undergoing stapedotomy at Bharath Medical College Hospital & Research Institute, Chennai. All patients underwent pre-operative CBCT followed by intraoperative assessment of the oval window niche. The CBCT and intraoperative findings were compared, focusing on the presence of a narrow or non-narrow oval window niche. Data were statistically analyzed using SPSS software, and agreement between CBCT and surgical findings was evaluated using Kappa statistics. Results: Among the 50 patients (mean age: 43.58 years), 10% exhibited a narrow oval window niche, while 90% had a non-narrow niche as per both CBCT and intraoperative findings. There was perfect agreement (Kappa = 1) between CBCT and surgical observations, with 100% sensitivity, specificity, and diagnostic accuracy. Conclusion: CBCT proved to be a highly accurate and reliable modality for preoperative assessment of the oval window niche in otosclerosis patients. The findings reinforce CBCT's value in surgical planning and its potential to minimize intraoperative complications.